Estimation of Communities and Tourists Willingness to Pay for Tsunami Disaster Mitigation of Marine Tourism in the Kalianda Coastal Area, South Lampung Regency - Permana Ari Soejarwo; Rismawaty Rusdi; Taryono Kodiran; Umi Muawanah (Jurnal Ilmu Lingkungan, 2021)
Indonesia coastal areas have considerable natural disaster potential including in Kalianda District South Lampung Regency. Natural disasters such as earthquakes, tsunamis and volcanic activity are likely to occur in coastal areas. The disaster has an impact on economic losses in the marine tourism area. In order to mitigate tsunami disasters in the marine tourism area of Kalianda District, South Lampung Regency, 3 (three) types of tsunami mitigation are needed, namely: construction of coastal protection, installation of the Tsunami Early Warning System (TEWS) and planting of coastal vegetation. This study aims to determine the value of willingness to pay (WTP) of community and tourists in supporting the management of the three types of tsunami disaster mitigation above by using economic valuation / Contingent Valuation Method (CVM). The results of this study indicate that the WTP value of community for coastal protection management is Rp 15.547/person/month while the WTP value of tourist is Rp 12.030/one time entry. Meanwhile, for the WTP value of TEWS management is obtained Rp 12.174/person/month. WTP value for the management of coastal vegetation is Rp 12.444/person/month. The WTP calculation is based on consideration of 3 (three) factors, namely age, income, livelyhood and education level. This research shows that the community and tourists are willing to pay for the management of the three types of tsunami disaster mitigation through BUMDes and entrance fees for marine tourism area. The three types of tsunami disaster mitigation can protect, provide security and calm to the community and tourists in the marine tourism area of Kalianda District, South Lampung Regency from future tsunami.